Penggunaan Design Thingking Model untuk Pencegahan Tindakan Bullying pada Santri di Pondok Pesantren ABC - Muhammad Haikal Badruzzaman; Fernanda Sisca Amelia; Asep Taryana Sujana (Jurnal Syntax Admiration, 2024)
It is important for an organization or institution to have an effective and quality violence prevention strategy in carrying out the vision and mission that has been made to realize the goals for the organization or institution itself. This study aims to find out the handling strategies carried out by the ABC Islamic Boarding School from the stage of student safety planning to supervision evaluation to improve environmental safety for its students. This research is a qualitative descriptive research that uses the design thinking method. The informants in this study are the principal, teachers, and students of the ABC Islamic Boarding School. This research is located at the ABC Islamic Boarding School. The data collection methods used are interviews, observations, and documentation studies. As a result, the application of the design thinking model has proven to be effective in identifying the root cause of the problem and creating innovative solutions to prevent bullying in the Islamic boarding school environment. Through the stages of empathy, definition, idea, prototype, and testing, the research team was able to understand the needs and challenges faced by the students. Bullying is bound to have bad consequences, not only for those who do it but especially for those who are targeted, affecting their personal, social, and educational aspects. Holding positive activities for students who can instill family values and solidarity, as well as organizing educational sessions about bullying during their stay at the pesantren, can help prevent this behavior from happening again in the future.